Impact of land-use changes on soil properties and carbon pools in India: A meta-analysis - Padbhushan, Rajeev; Kumar, Upendra; Sharma, Sheetal; Rana, D.S.; Kumar, Rajkishore; Kohli, Anshuman; Kumari, Priyanka; Parmar, Brajendra; Kaviraj, Megha; Sinha, Abhas Kumar; Annapurna, K.; Gupta, Vadakattu V. S. R. (Frontiers Media, 2022)
Land-use changes (LUC), primarily due to deforestation and soil disturbance, are one of the major causes of soil quality degradation and greenhouse gas emissions. Effects of LUC on soil physicochemical properties and changes in soil quality and land use management strategies that can effectively restore soil carbon and microbial biomass levels have been reported from all over the world, but the impact analysis of such practices in the Indian context is limited. In this study, over 1,786 paired datasets (for meta-analysis) on land uses (LUs) were collected from Indian literature (1990–2019) to determine the magnitude of the influence of LUC on soil carbon, microbial biomass, and other physical and chemical properties at three soil depths. Meta-analysis results showed that grasslands (36.1%) lost the most soil organic carbon (SOC) compared to native forest lands, followed by plantation lands (35.5%), cultivated lands (31.1%), barren lands (27.3%), and horticulture lands (11.5%). Our findings also revealed that, when compared to forest land, the microbial quotient was lower in other LUs. Due to the depletion of SOC stock, carbon dioxide equivalent (CO2 eq) emissions were significantly higher in all LUs than in forest land. Results also showed that due to the conversion of forest land to cultivated land, total carbon, labile carbon, non-labile carbon, microbial biomass carbon, and SOC stocks were lost by 21%, 25%, 32%, 26%, and 41.2%, respectively. Changes in soil carbon pools and properties were more pronounced in surface (0–15 cm) soils than in subsurface soils (15–30 cm and 30–45 cm). Restoration of the SOC stocks from different LUs ranged from a minimum of 2% (grasslands) to a maximum of 48% (plantation lands). Overall, this study showed that soil carbon pools decreased as LUC transitioned from native forestland to other LUs, and it is suggested that adopting crop-production systems that can reduce CO2 emissions from the intensive LUs such as the ones evaluated here could contribute to improvements in soil quality and mitigation of climate change impacts, particularly under Indian agro-climatic conditions.